2012
DOI: 10.1111/j.1757-1707.2011.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' perspectives for the development of a bioenergy industry in Ireland

Abstract: A survey of Irish farmers was conducted to identify farmers' opinions on energy crop production and to characterize potential adopters of energy crop cultivation in Ireland. One hundred and seventy-two surveys were completed from 25 counties in Ireland. Miscanthus (48%) and grass (30%) were the preferred crops for adoption of energy crop production. Potential adopters described themselves as having a significantly greater level of knowledge of energy crop production compared with other respondents. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…For SRC, 87.7% responded that they would not be willing, 11.9% responded that they would be willing and 0.4% noted that they already grew this crop. These results concur with evidence from Ireland where miscanthus was also identified to be of greater interest to farmers than SRC [22]. Analysing the data for the two crops together, 10.7% of farmers would be willing to grow both crops and 79.9% of farmers would not be willing to grow either crop.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…For SRC, 87.7% responded that they would not be willing, 11.9% responded that they would be willing and 0.4% noted that they already grew this crop. These results concur with evidence from Ireland where miscanthus was also identified to be of greater interest to farmers than SRC [22]. Analysing the data for the two crops together, 10.7% of farmers would be willing to grow both crops and 79.9% of farmers would not be willing to grow either crop.…”
Section: Resultssupporting
confidence: 82%
“…Whilst it has been noted that there are no absolute barriers to bioenergy in the EU, it is the non-technical challenges that are more likely to hold back production of suitable feedstocks [24]. A survey of 172 farmers in Ireland, from a wide range of farm types, showed that over 70% of farmers were interested in energy crops although the authors suggested that the method of dissemination for the survey had encouraged those interested in DECs to respond [22]. A motivation for adoption was the perceived profits for DECs.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenqvist, 2011). A survey carried out by Augustenborg et al (2012) has shown high willingness of farmers to adopt energy crops in Ireland, with over 70% of respondents indicating interest in producing energy crops.…”
Section: Justification For Willowmentioning
confidence: 99%
“…As Miscanthus is a perennial crop, this lifespan differs greatly from those of traditional crops which are cultivated from year to year providing the farmer with the opportunity to reallocate the land frequently to different crops. The long commitment of land to one single plant does not only limit the entrepreneurial freedom of the farmer which is seen as a major barrier to Miscanthus adoption by 7 of the reviewed papers [23,42,48,54,[56][57][58]. It also implies the fact that Miscanthus needs a minimum period to break even with the initial investment costs.…”
Section: Lifespanmentioning
confidence: 93%
“…Establishment of the plantation. The high upfront establishment costs are quoted as a major impediment for Miscanthus adoption [9,45,58,62]. However, the supply with detailed information about establishment cost is scarce in the examined literature.…”
Section: Costs Of Miscanthus Cultivationmentioning
confidence: 99%